B-Raf Regulation of Integrin α4β1-mediated Resistance to Shear Stress through Changes in Cell Spreading and Cytoskeletal Association in T Cells - Brown, Wells S. (American Society for Biochemistry and Molecular Biology, 2014)
The regulation of integrin-mediated adhesion is of vital importance to adaptive and innate immunity. Integrins are versatile proteins and mediate T cell migration and trafficking by binding to extracellular matrix or other cells as well as initiating intracellular signaling cascades promoting survival or activation. The MAPK pathway is known to be downstream from integrins and to regulate survival, differentiation, and motility. However, secondary roles for canonical MAPK pathway members are being discovered. We show that chemical inhibition of RAF by sorafenib or shRNA-mediated knockdown of B-Raf reduces T cell resistance to shear stress to α4β1 integrin ligands vascular cell adhesion molecule 1 (VCAM-1) and fibronectin, whereas inhibition of MEK/ERK by U0126 had no effect. Microscopy showed that RAF inhibition leads to significant inhibition of T cell spreading on VCAM-1. The association of α4β1 integrin with the actin cytoskeleton was shown to be dependent on B-Raf activity or expression, whereas α4β1 integrin affinity for soluble VCAM-1 was not. These effects were shown to be specific for α4β1 integrin and not other integrins, such as α5β1 or LFA-1, or a variety of membrane proteins. We demonstrate a novel role for B-Raf in the selective regulation of α4β1 integrin-mediated adhesion.